Secondary Neoplasms After Hematopoietic Cell Transplant for Sickle Cell Disease. Issue 12 (20th April 2023) - Eapen, Mary; Brazauskas, Ruta; Williams, David A.; Walters, Mark C.; St Martin, Andrew; Jacobs, Benjamin L.; Antin, Joseph H.; Bona, Kira; Chaudhury, Sonali; Coleman-Cowger, Victoria H.; DiFronzo, Nancy L.; Esrick, Erica B.; et al.
Abstract : PURPOSE: To report the incidence and risk factors for secondary neoplasm after transplantation for sickle cell disease. METHODS: Included are 1, 096 transplants for sickle cell disease between 1991 and 2016. There were 22 secondary neoplasms. Types included leukemia/myelodysplastic syndrome (MDS; n = 15) and solid tumor (n = 7). Fine-Gray regression models examined for risk factors for leukemia/MDS and any secondary neoplasm. RESULTS: The 10-year incidence of leukemia/MDS was 1.7% (95% CI, 0.90 to 2.9) and of any secondary neoplasm was 2.4% (95% CI, 1.4 to 3.8). After adjusting for other risk factors, risks for leukemia/MDS (hazard ratio, 22.69; 95% CI, 4.34 to 118.66; P = .0002) or any secondary neoplasm (hazard ratio, 7.78; 95% CI, 2.20 to 27.53; P = .0015) were higher with low-intensity (nonmyeloablative) regimens compared with more intense regimens. All low-intensity regimens included total-body irradiation (TBI 300 or 400 cGy with alemtuzumab, TBI 300 or 400 cGy with cyclophosphamide, TBI 200, 300, or 400 cGy with cyclophosphamide and fludarabine, or TBI 200 cGy with fludarabine). None of the patients receiving myeloablative and only 23% of those receiving reduced-intensity regimens received TBI. CONCLUSION: Low-intensity regimens rely on tolerance induction and establishment of mixed-donor chimerism. Persistence of host cells exposed to low-dose radiation triggering myeloid malignancy is one plausible etiology. Pre-existing myeloid mutations and prior inflammation may also contribute but could not be studied using our data source. Choosing conditioning regimens likely to result in full-donor chimerism may in part mitigate the higher risk for leukemia/MDS.